Breeding Tetraploid Paspalum simplex: Hybridization, Early Identification of Apomicts and Impact of Apomixis on Hybrid Performance - Brugnoli, Elsa Andrea; Martinez, Eric Javier; Ferrari Usandizaga, Silvana Consuelo; Zili, Alex Leonel; Urbani, Mario; Acuña, Carlos Alberto (Wiley, 2023)
Apomictic grasses predominate among tropical forages, and specific breeding techniques are needed for their genetic improvement. The objectives of this study were (i) to generate hybrids by crossing tetraploid sexual and apomictic Paspalum simplex Morong genotypes, (ii) to develop a technique based on molecular markers for early identification of apomictic hybrids, and (iii) to determine the relationship between mode of reproduction and performance of hybrids. Crosses were made between two induced sexual and seven apomictic tetraploid plants. Identification of apomictic hybrids during seedling stage was performed using a marker linked to apomixis, and by flow cytometric seed analysis. Hybrids were evaluated under field conditions for plant diameter and height, initial growth, and seasonal regrowth during two consecutive growing seasons. Sexual tetraploid plants used as female parents behaved as allogamous, since 95% of the progeny had male-specific markers. The ratio between apomictic and sexual hybrids differed from 1:8.7 to 1:0.6 among crosses, with a mean of 1:2.4. There was a 96% coincidence between the use of the apomixis-linked marker and flow cytometric seed analysis. A technique based on the use of early DNA isolation and the amplification of a molecular marker linked to apomixis was developed. We found no overall difference between apomictic and sexual hybrids for the evaluated traits, except for fall regrowth in the first year, for which apomictic hybrids were superior. Generation of large tetraploid hybrid progenies is possible in P. simplex. Segregation for mode of reproduction depends on parents involved. Agronomic performance is not related to reproductive mode among tetraploid hybrids.